Immunologic and nonimmunologic sclerodermal skin conditions - review - Bobeica, Carmen; Niculet, Elena; Craescu, Mihaela; Parapiru, Elena-Laura; Corduneanu-Luca, Andreea Mioara; Debita, Mihaela; Pelin, Ana Maria; Tiutiuca, Carmen; Vasile, Claudiu Ionut; Nicolescu, Alin Codrut; Miulescu, Magdalena; Balan, Gabriela; et al. (Frontiers in Immunology, 2023)
Scleroderma-like cutaneous lesions have been found in many pathological conditions and they have the clinical appearance of sclerotic or scleroatrophic lesions. Affected skin biopsies described histopathological changes similar to those of scleroderma located strictly on the skin or those of systemic sclerosis. These skin lesions can befound in inflammatory diseases with autoimmune substrate (generalized morphea, chronic graft versus host disease, eosinophilic fasciitis), tissue storage diseases (scleredema, scleromyxedema, nephrogenyc systemic fibrosis, systemic amyloidosis), metabolic diseases (porphyrya cutanea tarda, phenylketonuria, hypothyroidism, scleredema diabeticorum), progeroid syndromes. Given the multiple etiologies of sclerodermal lesions, a correct differential diagnosis is necessary to establish the appropriate treatment.